A review of atmospheric aging of sea spray aerosols: Potential factors affecting chloride depletion. (1st December 2022) - Su, Bojiang; Wang, Tao; Zhang, Guohua; Liang, Yue; Lv, Chen; Hu, Yaohao; Li, Lei; Zhou, Zhen; Wang, Xinming; Bi, Xinhui
Abstract: Sea spray aerosol (SSA) is the largest natural source of aerosols in the troposphere, and has profound potential significance for climate change, visibility, and human health. It has been shown that the aging process of SSA in the atmosphere by various chemical transformations can result in chloride depletion, releasing HCl, Cl2, ClNO2, etc. These active chlorine species can significantly affect the atmospheric oxidizing capacity in the troposphere and stratosphere. Compared with the fresh SSA, the aged SSA exhibits distinctly different behaviors in hygroscopicity, optical properties, and cloud condensation nuclei (CCN)/ice nuclei (IN) activity. The literature over the past three decades has dramatically broadened the knowledge of the chloride depletion and improved our understanding of the interconnection between the ocean, atmosphere, and SSA. This paper provides a critical review and synthesis of field observations and laboratory studies on chloride depletion of SSA. More specifically, we summarize recent discoveries in the various types of heterogeneous reactions that lead to chloride depletion, the experimental methodology, mechanism and potential influencing factors. General conclusions are drawn that the acidic species, particle size, types and mixing state, and environmental factors have a significant impact on chloride depletion of SSA. Particularly, the difference in mixing state between individual SSA plays a crucial role in chloride depletion but is still ambiguous. Finally, we conclude with a summary on the results and inadequacy of current laboratory and field studies on chlorine depletion of SSA and some future research perspectives. Graphical abstract: Image 1 Highlights: Measurement techniques and assessment methodology for chloride depletion of sea spray aerosol (SSA) are presented. Heterogeneous reactions of chloride depletion of SSA are comprehensively reviewed. Potential factors affecting chloride depletion of SSA are discussed.